The use of literature to promote language, culture and personal growth development :|bA survey on TESL and ESL undergraduates in UNIMAS - Kueh, Yien Ee. (Universiti Malaysia Sarawak, UNIMAS, 2008)
T his study aimed to investigate TESL and ESL undergraduates’ personal views towards literature and the benefits of studying literature sub jects in UNIMAS. The se benefits were based on Carter and Long ’s model (1991) , namely language, cultural and personal growth development. 150 full - time TESL and ESL undergraduates who had taken literature courses for at least two years in their educationa l programmes were chosen as the participants for this study . Data were collected through 5 - point Likert scale questionnaire and semi - structured interview. After the exposure to literature in UNIMAS, the participants developed a gradual liking towards lite rature as visual tools such as movies and drama were used to help them in comprehending the literary texts. In terms of language development, the participants ’ vocabulary repertoire was enriched and they were trained to make prediction and interpretation based on contextual clues. Culturally, the TESL and ESL undergraduates were enriched with cultural knowledge from local and foreign countries which led to an appreciation and tolerance with the cultural differences between people. Furthermore , the partic ipants were personally engaged with the literary texts as they were able to relate the literary texts with their personal experiences and developed greater sensitivity towards other people’s feeling s especially during interaction